PERBEDAAN KARAKTERISTIK MENTAL ATLET SEA GAMES DI LIHAT DARI SISI GENDER - Yahya Eko Nopiyanto; Alimuddin Alimuddin (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
The objective of this study is to investigate differences the psychological characteristic of Indonesian SEA Games athletes in terms of team sports based on sex. This research employed the quantitative approach using the survey method with a restrospective causal-comparative design. This research was population research. All subjects in the population were included in this research with a total of 83 athletes while 43 male athletes and 40 female athletes were from team sports. The data were collected using the Psychological Skills Inventory for Sports (PSIS) questionnaire and analyzed using the independent sample t test at the significance level of 0.05. The research findings revealed that there were significant differences in the psychological characteristics of Indonesian SEA Games athletes in terms of team sports based on sex with the mean score of male athletes = 150.1395 and female atheles = 139.3500 and sig. values = 0.000 < 0.05. There were significant differences in the psychological characteristics of Indonesian SEA Games athletes in terms of team sports based on sex.